Ideological Self-obsession and the Burden of Victims. Review of the ISC case - Marković, Saša M. (Napredak, 2022)
In this paper, we intend to present the anchor points of the Ustasha ideology that used to be the foundation of the Independent State of Croatia. This puppet creation, made on the ruins of the Yugoslav monarchy, promoted nationalist fury. Its intention was to create an ethnically clean state in the territory where, in geopolitical terms, it was impossible without an exodus and execution of the population with other nationalities. Commitment to anti-Semitism was used by this state as an impetus for national intolerance towards Serbs and it largely exceeded the intended pattern of the Nazi Holocaust. The remembrance culture was created presenting the past as a decades long struggle, the cause of which was mostly attributed to Serbs. The culmination was the Yugoslav dungeon. Young generations were brought up and educated to represent national purity and to serve the Supreme Leader loyally. The personality cult was the crown of such furious ideology that, in its decisive intention to reach its realization, despite the resistance of the reality, used all available means. The war and uncontrollable hatred were favourable circumstances for the final solution to the Croatian question that, in the Ustasha ideology, was impossible without the thorough solution to the Serbian factor. The consequences of this were innumerable victims.